Expecting the Unexpected: Documenting Accidentology in the Philippines - Politsch, Barbara (Kasarinlan: Philippine Journal of Third World Studies; Vol 32 No 1,2 (2017): TWSC and Forty Years of Critical Scholarship, 2018)
The commentary tackles the first six documentaries of the TWSC-UdM Video Documentary Internship Program, the majority of which were made under the program “Student for Development.” From 2015 up to 2017, production of TWSC-UdM documentaries is an activity of the network called REINVENTERRA (Réseau d’études internationales sur la valorisation et l’exploitation de la nature, des terres et des ressources en Afrique, Asie et Amérique latine, or International Research Network on Exploitation and Usage of Nature, Land, and Resources in Africa, Asia and Latin America). The documentaries are available online at the TWSC’s Youtube channel (https://bit.ly/2tt5XsB).